2014
DOI: 10.1111/jph.12250
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacillus altitudinis as a New Causative Agent of Bacterial Soft Rot

Abstract: A total of 67 bacterial isolates were obtained from apple and pear fruits with signs of soft rot collected from Egyptian markets. Pathogenicity tests showed that 25 isolates (37%) were pathogenic to apple and pear fruits, with considerable variation of virulence. Among these isolates, 16 (64%) were Gram‐positive, motile, spore‐forming long rods and were identified as members of the genus Bacillus based on an API test. In addition, five isolates (20%) were Gram‐negative, non‐spore‐forming, motile, oxidase and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…altitudinis has been recently characterized as a new causative agent of bacterial soft rot on apple and pear fruit (Elbanna et al 2014). Accordingly, we tested whether the B. altitudinis JSCX-1 isolated in this study could cause soft rot on these fruit.…”
Section: Discussionmentioning
confidence: 99%
“…altitudinis has been recently characterized as a new causative agent of bacterial soft rot on apple and pear fruit (Elbanna et al 2014). Accordingly, we tested whether the B. altitudinis JSCX-1 isolated in this study could cause soft rot on these fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Moratoğlu, Demĩrbağ, and Sezen () found that the investigated P. putida strains Ld3 and LD4 grew in 4%NaCl and at 37ºC, were positive for acid production from glucose and did not produce acid from maltose, mannitol and raffinose. Moreover, B. altitudinis was first reported as a soft rot pathogen on apple and pear fruits in Egypt; thus, the pathogen could macerate potato tubers (Elbanna et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…All strains were screened for enzymes related to maceration and soft rot using the method of Chatterjee, Cui, Liu, Dumenyo, and Chatterjee (1995), Joko, Subandi, Kusumandari, Wibowo, and Priyatmojo (2014) and Elbanna et al (2014). The bacterial isolates were inoculated onto pectate lyase (hydrolysis), containing 1% polygalectoronic acid, cellulase, protease and crystal violet pectate medium (CVP) Himedia® containing 1.8% sodium polypectate (non-hydrolysis); crystal violet inhibits the growth of Gram-positive bacteria.…”
Section: Enzyme Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some species of Bacillus, Pseudomonas, Acremonium and Humicola could promote plant growth due to their antagonistic activity, the production of IAA or specific substance to activate resistance for control of diseases (Dharni et al 2014;Hassan et al 2015;Khabbaz et al 2015;Wenhsiung 2009;Yang et al 2014). On the other side, some species of these genera showed negative effect on plant growth due to their broadspectrum pathogenic activity (Elbanna et al 2014;Furuya et al 2005;Iakovleva et al 2013;Racedo et al 2013;Zhang et al 2014). Additionally, the report of other plant suggested that the harmful microbes were increased with the decrease of beneficial microbes under monocultivated conditions, and the soil ecological function was affected (Lin et al 2015).…”
Section: Discussionmentioning
confidence: 99%